P65 | (YS) INVESTIGATING THE EFFECTS OF THE SECRETOME FROM HUMAN AMNIOTIC MESENCHYMAL STROMAL CELLS ON INFLAMMASOME ACTIVATION (European Journal of Histochemistry)
Macrophages play a pivotal role in inflammation and, upon exposure to stimuli such as lipopolysaccharides (LPS), they activate the NLRP3 inflammasome – a multiprotein complex of the NOD-like receptor family. This activation drives macrophage polarization toward the pro-inflammatory M1 phenotype through metabolic reprogramming, reactive oxygen species (ROS) production, and the release of pro-inflammatory cytokines1. The canonical activation pathway of NLRP3 involves the oligomerization of ASC (apoptosis-associated speck-like protein containing a CARD), forming cytosolic aggregates known as ASC specks, and triggers caspase-1 activation and IL-1β maturation2. We previously demonstrated that the secretome from human amniotic mesenchymal stromal cells (hAMSC), also known as conditioned medium (CM-hAMSC), affects macrophage polarization by promoting a shift from the pro-inflammatory M1 phenotype to the anti-inflammatory M2 phenotype3. This study investigates whether CM-hAMSC can modulate inflammasome activation in M1 macrophages. Monocytes were differentiated into M1 macrophages using GM-CSF for 5 days and then stimulated with LPS and ATP in presence or absence of CM-hAMSC. After 5 h, inflammasome activation was evaluated as IL-1β release, ASC speck formation and mitochondrial ROS levels through ELISA, fluorescence microscopy and flow cytometry analyses. CM-hAMSC significantly reduced IL-1β secretion and ROS accumulation, with a slight decrease in ASC speck formation. These findings support the anti-inflammatory role of CM-hAMSC and highlights the need for more detailed mechanistic studies.